Michèle Hayeur Smith and Alexandra Sanmark, eds., The Hidden Lives of Viking Women: Archaeological and historical perspectives - Rowlatt, Linnéa (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
Linnéa Rowlatt reviews the edited volume from Michèle Hayeur Smith and Alexandra Sanmark entitled The Hidden Lives of Viking Women: Archaeological and historical perspectives.